2000
DOI: 10.1177/009365000027004004
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and Ethnic Media Use

Abstract: Ethnicity continues to be a political and social force on the national and international scenes. After a discussion of the literature on ethnicity and communication, this article tracks a panel representing 13 different White ethnic groups in a metropolitan area. Data were collected every 4 years, beginning in 1976 and continuing through 1992. In 1976, 13 ethnic groups were surveyed, and 11 groups were tracked in subsequent surveys. Although each wave collected data unique to that period, all surveys included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 53 publications
2
65
0
8
Order By: Relevance
“…Kim (1977Kim ( , 1988 postulated that immigrants' accessibility to American media and acculturation motivation predicts their exposure to American media. Research supports these propositions, establishing media use as an indicator of acculturation (Jeffres, 2000;Moon & Park, 2007;Shoemaker, Reese, & Danielson, 1985;Subervi-Velez, 1986;Tan, 1983). Shoemaker et al, for instance, suggested that the use of English language media indicates greater acculturation to American society.…”
Section: Hypothesis and Research Questionmentioning
confidence: 99%
“…Kim (1977Kim ( , 1988 postulated that immigrants' accessibility to American media and acculturation motivation predicts their exposure to American media. Research supports these propositions, establishing media use as an indicator of acculturation (Jeffres, 2000;Moon & Park, 2007;Shoemaker, Reese, & Danielson, 1985;Subervi-Velez, 1986;Tan, 1983). Shoemaker et al, for instance, suggested that the use of English language media indicates greater acculturation to American society.…”
Section: Hypothesis and Research Questionmentioning
confidence: 99%
“…Or are underrepresentation, marginalization and negative portrayal leading to marginalization and separative acculturation strategies and social disintegration (Berry 1992;Gerbner 1993;Signorielli 1984;Sreberny 1999;Christiansen 2004;Weber-Menges 2005;Deuze 2006)? A bad representation of ethnic minority groups will probably not foster the feeling of being at home in a society and the willingness to make a contribution to social integration (Jeffres 2000;Maurer and Reinemann 2006).…”
Section: Deficiencies In Media Representation and Their Perceptionmentioning
confidence: 99%
“…Academic publications in communication science regularly highlight deficiencies in the representation of migrants in media coverage, in studies mostly based on content analyses (ter Wal 2004). Furthermore, research findings suggest that the perception of such deficiencies by migrants themselves influence their group or ethnic identity and their identification with the majority (Jeffres 2000) as well as their media use (Trebbe 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This process has been called "bridging social capital" by Putnam (2000) and is considered a pre-requisite for social-cultural participation or integration into the host society. On the other hand, media from the home country help immigrants connect to their original culture and thus play a prominent role in the preservation of their own cultural heritage and strengthen their inter-group solidarity (Greenberg, 1983;Subervi-Velez, 1986;Greenberg, 1994;Kim, 1995;Hall, Anten and Cakim, 1999;Appadurai, 1997;Rios and Gaines, 1998;Jeffres, 2000). In this case, the function of the media concerns communication within a given cultural group.…”
Section: The Turkish Diaspora's Transnational Communication Processesmentioning
confidence: 99%